Sustainable mobility scale: A contribution for sustainability assessment systems in urban mobility - Suélen Bebber (Cleaner Engineering and Technology, 2021)
The sustainable development of a city directly connects to the conditions of urban mobility. It is essential for public and private managers to know the citizens' perceptions of their mobility in the city. To this end, this research aims to develop and validate a scale to evaluate mobility according to the sustainable dimensions established by ISO 37120, ISO 37122, and the UN Sustainable Development Goals. The Sustainable Mobility scale (SMob scale) was developed from concepts underlying objective indicators to identify subjective attributes related to citizen perception. The final scale resulted in 21 attributes distributed in 6 dimensions through exploratory and confirmatory factor analysis. As an additional contribution, a gap was identified related to urban mobility attributes for reduced mobility people. Given the changes necessary to promote an effective mobility strategy in South American countries, this study contributes to translating citizens' perceptions to identify weaknesses and then plan and propose improvements, contributing to sustainable mobility development.